194k views
2 votes
For the polynomial below, -1 is a zero.

-
g(x)=x^3 - 5x^2 + 7x + 13
Express g(x) as a product of linear factors.
g(x)=

1 Answer

6 votes

Answer:

g = 7 + 13x-1 + -5x + x2

Explanation:

Simplifying

g(x) = x3 + -5x2 + 7x + 13

Multiply g * x

gx = x3 + -5x2 + 7x + 13

Reorder the terms:

gx = 13 + 7x + -5x2 + x3

Solving

gx = 13 + 7x + -5x2 + x3

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by 'x'.

g = 13x-1 + 7 + -5x + x2

Simplifying

g = 13x-1 + 7 + -5x + x2

Reorder the terms:

g = 7 + 13x-1 + -5x + x2

User Captain Whippet
by
4.9k points